Maintenance of World Health Organization risk drinking level reductions and posttreatment functioning following a large alcohol use disorder clinical trial - Witkiewitz, Katie; Falk, Daniel E.; Litten, Raye Z.; Hasin, Deborah S.; Kranzler, Henry R.; Mann, Karl; O'Malley, Stephanie S.; Anton, Raymond F. (Alcoholism, 2019)
Background Reductions in the World Health Organization (WHO) risk drinking levels have been proposed as an alternative primary outcome for alcohol clinical trials. Yet, little is known about whether reductions in WHO risk drinking levels can be maintained over time. The current study examined whether reductions in WHO risk drinking levels were maintained for up to 1 year following treatment, and whether reductions over time were associated with improvements in functioning. Methods Secondary data analysis of individuals with alcohol dependence (n = 1,226) enrolled in the COMBINE study, a multisite, randomized, placebo-controlled clinical trial. Logistic regression was used to examine the maintenance of end-of-treatment WHO risk level reductions and WHO risk level reductions at the 1-year follow-up. Repeated-measures mixed models were used to examine the association between WHO risk level reductions and functional outcomes over time. Results Achieving at least a 1- or 2-level reduction in risk by the end of treatment was significantly associated with WHO risk level reductions at the 1-year follow-up assessment (p < 0.001). Among individuals who achieved at least a 1-level reduction by the end of treatment, 85.5% reported at least a 1-level reduction at the 1-year follow-up. Among individuals who achieved at least a 2-level reduction by the end of treatment, 77.8% reported at least a 2-level reduction at the 1-year follow-up. WHO risk level reductions were associated with significantly lower alcohol consumption, better physical health (p < 0.01), and fewer alcohol-related consequences (p < 0.001) up to 1 year following treatment. Conclusions One- and 2-level reductions in WHO risk levels during alcohol treatment were maintained after treatment and associated with better functioning over time. These findings support the use of the WHO risk level reductions as an outcome measure that reflects clinically significant improvement in how individuals seeking treatment for alcohol use disorder feel and function.